Literature Review: Analysis of Saponins in Several Plants by HPLC Method and Its Utilization in Pharmaceutical Products - Prasasty, Vony Intan (Newinera Publisher, 2024)
This research aims to determine the content of saponin compounds found in several types of plants and their benefits for health. This research uses computer equipment and the Google Scholar database, Research Gate, NJC journal, Science Direct. The type of research used is an article review using data sources directly collected by the researcher. The data search was carried out through a Google Scholar database, using the keywords